Evaluating the efficacy of vilazodone in achieving remission in patients with major depressive disorder. (March 2015) - Citrome, Leslie; Gommoll, Carl P.; Tang, Xiongwen; Nunez, Rene; Mathews, Maju
<x xml:space="preserve">Abstract</x> The aim of this study was to evaluate the efficacy of vilazodone using different definitions of remission. Post-hoc analyses were carried out using data from an 8-week, multicenter, randomized, double-blind, placebo-controlled trial of vilazodone 40 mg/day in adults with major depressive disorder (NCT01473394). The primary efficacy endpoint was a mean change in the Montgomery–Åsberg Depression Rating Scale (MADRS) total score; additional measures included the Clinical Global Impressions-Severity (CGI-S) and Hamilton Rating Scale for Anxiety (HAMA) scores. In addition to treatment response (MADRS≥50% improvement), post-hoc analyses were carried out for remission of depressive symptoms [MADRS score⩽10; MADRS⩽5 (complete remission)], anxiety symptoms (HAMA⩽7), and combined depression and anxiety symptoms (MADRS/HAMA⩽10/⩽7), as well as for overall symptom severity (CGI-S=1). Odds ratios (ORs) and numbers needed to treat (NNTs) were also calculated. Significant outcomes were obtained with vilazodone versus placebo for MADRS response (50.6 vs. 33.3%, OR=2.04, P<0.001, NNT=6), remission (34.0 vs. 21.8%, OR=1.82, P=0.003, NNT=9), and complete remission (18.2 vs. 8.3%, OR=2.42, P=0.002, NNT=11). More patients receiving vilazodone rather than placebo also met remission criteria for HAMA (48.8 vs. 35.2%, OR=1.82, P=0.002, NNT=8), MADRS/HAMA (32.1 vs. 20.4%, OR=1.83, P=0.004, NNT=9), and CGI-S (24.1 vs. 11.5%, OR=2.41, P<0.001, NNT=8). Treatment with vilazodone 40 mg/day may help adult patients with major depressive disorder achieve remission of depression and/or anxiety symptoms.